An Extreme Point Algorithm For A Local Minimum Solution To The Quadratic Assignment Problem - Fedjki, C.A. (2020)
In this paper the network structure of basic solutions to the quadratic assignment problem (QAP) is revisited. The concept of a relative local star minimum is introduced. Results characterizing a relative local star minimum are obtained. Then an extreme point algorithm for QAP is proposed.